COMPUTER MODELLING OF AUTOMATIC CONTROL PROCESS OF DISTILLATION COLUMN - Drevetskiy, Volodymyr; Ivanchuk, Vasyl (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2016)
Here the process of distillation in the production of ethanol is considered. Developed a mathematical model of determination and regulation of ratio of distillation column and its impact on concentration and quantitative composition of impurities of outgoing product. Suggested a method of calculation and schematic diagram of ratio automatic control and regulation in order to improve the quality of the final product and to reduce the energy costs.